2014
DOI: 10.15252/embj.201488117
|View full text |Cite
|
Sign up to set email alerts
|

Paternal RNA contributions in the Caenorhabditis elegans zygote

Abstract: Development of the early embryo is thought to be mainly driven by maternal gene products and post-transcriptional gene regulation. Here, we used metabolic labeling to show that RNA can be transferred by sperm into the oocyte upon fertilization. To identify genes with paternal expression in the embryo, we performed crosses of males and females from divergent Caenorhabditis elegans strains. RNA sequencing of mRNAs and small RNAs in the 1-cell hybrid embryo revealed that about one hundred sixty paternal mRNAs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 56 publications
(75 reference statements)
1
53
1
Order By: Relevance
“…This study, as well as previous studies (Alcazar et al, 2008;Ashe et al, 2012;Grishok et al, 2000;Luteijn et al, 2012;Shirayama et al, 2012;Stoeckius et al, 2014), clearly demonstrates that mutator-dependent silencing information inherits through both the paternal and maternal lineages. It is, however, not clear how this memory is precisely transmitted.…”
Section: Parental Memory Of Rnaesupporting
confidence: 83%
“…This study, as well as previous studies (Alcazar et al, 2008;Ashe et al, 2012;Grishok et al, 2000;Luteijn et al, 2012;Shirayama et al, 2012;Stoeckius et al, 2014), clearly demonstrates that mutator-dependent silencing information inherits through both the paternal and maternal lineages. It is, however, not clear how this memory is precisely transmitted.…”
Section: Parental Memory Of Rnaesupporting
confidence: 83%
“…Work in model organism Caenorhabditis elegans has identified hundreds of paternally derived mRNA present in the 1-cell embryo, before initiation of transcription (Stoeckius et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, both coding and non-coding RNAs have been well characterized in sperm (Jodar et al 2013), and it has been revealed that sperm can carry diverse RNA species (including mRNAs and small RNAs, some of which are sperm specific) to the fertilized zygote (Ostermeier et al 2004, Stoeckius et al 2014, indicating that these RNAs may play a unique paternal role in the development of zygotes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pseudogene-derived piRNAs complementary to protein-coding genes, which may regulate the expression of their parent gene in the male germ line, have been identified in the human sperm (Krawetz et al 2011, Pantano et al 2015. Moreover, Stoeckius and coworkers found that approximately half of all assayed endogenous piRNAs and siRNAs of 1-cell embryos in Caenorhabditis elegans are of sperm origin (Stoeckius et al 2014). The enrichment of tRNA-derived small RNAs (tsRNAs) in the sperm was first described in mice (Peng et al 2012), and then extended to humans, rats and rabbits .…”
Section: Introductionmentioning
confidence: 99%